2019
DOI: 10.1039/c9cc08509b
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in designing PROTACs for selective and potent degradation of HDAC6

Abstract: HDAC6 (histone deacetylase 6) catalyses the deacetylation of non-histone substrates, and plays important roles in cell migration, protein degradation and other cellular processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 24 publications
0
66
0
Order By: Relevance
“…Accordingly, HDAC6 inhibitors could be further tested in combination with TKIs or other molecules capable of targeting BCR-ABL such as bafetinib, rebastinib, tozasertib, danusertib, HG-7-85-01, GNF-2, and -5 molecules, and 1, 3, 4 thiadiazole derivatives, to potentially reduce resistance to treatment [200]. In the future, further development of selective PROTAC E3 ubiquitin ligase degraders triggering HDAC6 degradation [201] will provide further therapeutic options against various types of cancer, including CML.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, HDAC6 inhibitors could be further tested in combination with TKIs or other molecules capable of targeting BCR-ABL such as bafetinib, rebastinib, tozasertib, danusertib, HG-7-85-01, GNF-2, and -5 molecules, and 1, 3, 4 thiadiazole derivatives, to potentially reduce resistance to treatment [200]. In the future, further development of selective PROTAC E3 ubiquitin ligase degraders triggering HDAC6 degradation [201] will provide further therapeutic options against various types of cancer, including CML.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, HDAC6 inhibitors could be further tested in combination with TKIs or other molecules capable of targeting BCR-ABL such as bafetinib, rebastinib, tozasertib, danusertib, HG-7-85-01, GNF-2 and -5 molecules, and 1, 3, 4 thiadiazole derivatives, to potentially reduce resistance to treatment [193]. In the future, further development of selective PROTAC E3 ubiquitin ligase degraders triggering HDAC6 degradation [194] will provide further therapeutic options against various types of cancer, including CML.…”
Section: Resultsmentioning
confidence: 99%
“…All of these PROTACs have incorporated the HDAC6-selective inhibitor Nexturastat A and utilised “click” chemistry to conjugate the inhibitor to the E3 ligase ligand. A co-crystal structure of HDAC6 with Nexturastat A revealed that it binds via a y-shaped conformation, with the hydroxamic acid zinc binding group positioned inside the binding pocket for chelation to the zinc ion, and both the terminal benzene ring and aliphatic carbon chain protruding from the pocket, interacting with the isoform-specific hydrophobic surface rim of HDAC6 [ 133 , 193 ]. The latter surface exposed components thus served as ideal handles to build out from.…”
Section: Hdac Proteolysis-targeting Chimeras (Protacs)mentioning
confidence: 99%
“…The latter surface exposed components thus served as ideal handles to build out from. In successive works, the Rao group investigated both such positions, tethering pomalidomide via PEG linkers to both the aliphatic chain and benzene ring of Nexturastat A, synthesising two sets of degraders [ 193 , 194 ]. Overall, they found that functionalising from both locations of Nexturastat A produced HDAC6-selective degraders.…”
Section: Hdac Proteolysis-targeting Chimeras (Protacs)mentioning
confidence: 99%